UAV Architecture for Patrolling Air in Geotourism Zone at Disaster Risk with the Characteristics of GPS Signal Limit - Sartono Sartono; Iwan Hermawan; Gita Hindrawati (Research Synergy Foundation, 2023)
The development of geotourism is a trend in the field of tourism that is always being developed. The exoticism of natural tours in the environment of geothermal and volcanology activities will be proportioned to the potential risks that appear. The records of tracking from several countries show the fatal conditions from the effects of carbon dioxide emissions such as H2S, SO2, and CO that are emitted from unexpected geophysical activity, odorless so that they are not detected properly in geotourism zones that cause casualties of inhabitant and tourist. The aim of this paper is to provide a reference of the framework for the drone explore architecture for the requirement of monitoring in the environmental conditions of the limited GPS signal. This study implemented the Research & Development (R&D) method by using the Zachman framework. The study found that the development of the Early Warning System (EWS) as a part of mitigation using robotic technology such as the UAV drone becomes the solution requirement of the problem because the drone is capable of carrying sensors that detect harmful gases with a radius that is relatively low. The drone sensor will process the gas data with the permitted threshold gas ratio and send the collected data to the administration system. This case becomes a part of the disaster mitigation process in the geotourism field.